2010
DOI: 10.1021/cm903659g
|View full text |Cite
|
Sign up to set email alerts
|

Cd Substitution in MxZn4−-xSb3: Effect on Thermal Stability, Crystal Structure, Phase Transitions, and Thermoelectric Performance

Abstract: The effects of Cd substitution in M x Zn4−x Sb3 on the high-temperature thermal stability, low-temperature phase transitions and thermoelectric properties have been studied on three samples with a substitution degree of 0.1, 1, and 2 at % Cd (x = 0.004, 0.04, 0.08). The high-temperature thermal stability in atmospheric air of a 1% substituted sample is compared with an unsubstituted Zn4Sb3 sample. Multitemperature synchrotron powder diffraction data reveals that while only ∼42 wt % of the original Zn4Sb3 phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 28 publications
(67 reference statements)
3
47
2
Order By: Relevance
“…This microscopic mechanism explains the physical reason why the thermoelectric performance of zinc antimony is sensible to slight variation in Zn composition. This is consistent with experimental observations [23] and is applicable to super-ionic frameworks in large lattice (e.g.…”
supporting
confidence: 92%
“…This microscopic mechanism explains the physical reason why the thermoelectric performance of zinc antimony is sensible to slight variation in Zn composition. This is consistent with experimental observations [23] and is applicable to super-ionic frameworks in large lattice (e.g.…”
supporting
confidence: 92%
“…proposed by Kim et al the highest values reported so far on Zn-Sb based materials [11,24] . Since the doping amount of…”
Section: Thermoelectric Properties Of β-Zn4sb3 Under Thermal Cyclingmentioning
confidence: 90%
“…The decomposition of the Zn4Sb3 phase has been studied quantitatively using synchrotron powder X-ray diffraction (PXRD) [22][23][24][25][26] as well as by extensive evaluation of physical properties [27,28] . Attempts have also been made to substitute the Zn-sites with various elements such as Mg [22] , Cd [23,24,29] , and Pb [25] . The results showed that these doped samples are more stable than the non-doped sample under thermal cycling and during heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be mentioned that doping of Zn 4 Sb 3 has been shown by Iversen et al as a way to improve the stability. [14,15] In the present work, we study the degradation behavior of quench synthesised β-Zn 4 Sb 3 by heating the sample in argon atmosphere while measuring high resolution synchrotron powder X-ray diffraction (PXRD) data.…”
Section: Introductionmentioning
confidence: 99%